Identification of the IL-17 Receptor Related Molecule IL-17RC as the Receptor for IL-17F - Kuestner, Rolf E. (2007)
The proinflammatory cytokines IL-17A and IL-17F have a high degree of sequence similarity and share many biological properties. Both have been implicated as factors contributing to the progression of inflammatory and autoimmune diseases. Moreover, reagents that neutralize IL-17A significantly ameliorate disease severity in several mouse models of human disease. IL-17A mediates its effects through interaction with its cognate receptor, the IL-17 receptor (IL-17RA). We report here that the IL-17RA-related molecule, IL-17RC is the receptor for IL-17F. Notably, both IL-17A and IL-17F bind to IL-17RC with high affinity, leading us to suggest that a soluble form of this molecule may serve as an effective therapeutic antagonist of IL-17A and IL-17F. We generated a soluble form of IL-17RC and demonstrate that it effectively blocks binding of both IL-17A and IL-17F, and that it inhibits signaling in response to these cytokines. Collectively, our work indicates that IL-17RC functions as a receptor for both IL-17A and IL-17F and that a soluble version of this protein should be an effective antagonist of IL-17A and IL-17F mediated inflammatory diseases.